Numerical study on heat absorbing MHD radiating and reacting flow past an impulsively moving vertical plate with ramped temperature and concentration with Hall current - Prabhakar Reddy, B.; Makinde, O. D. (International journal of computational methods in engineering science and mechanics, 2022)
In this paper, we made elaborate investigation of the Hall current and radiation effects on MHD heat absorbing unsteady natural convection flow of a viscous incompressible electrically conducting fluid past an impulsively moving infinite vertical plate with ramped temperature and concentration in the presence of first order chemical reaction. The constructing coupled PDEs of the model along with initial and boundary conditions are solved numerically by utilizing the robust FEM. The effects of significant parameters on the primary and secondary velocities, temperature and concentration within the boundary layer are examined. The computational assessment of the primary and secondary shear stresses, rate of heat and mass transfer at the plate surface are put in tabular form. The thermal and mass buoyancy effects elevate both primary and secondary velocity components whilst reverse trend takes place when radiation and chemical reaction parameters are increased. Both primary and secondary velocity components decrease with increasing magnetic parameter whilst opposite trend are noticed with increasing Hall parameter. An increase in Prandtl number and radiation parameter results to reduce temperature distribution. The concentration distribution decreases with increase in Schmidt number and chemical reaction parameter. The significant difference between the fluid velocities is noticed due to the ramped and isothermal boundary conditions.